If cosec theta - cot theta = 1/3 then find the value of ( cosec theta + cot theta)

cosec θ - cot θ = 1 / 3 (given)

now, cosec^{2 }θ - cot^{2}θ = 1

⇒ (cosec θ - cot θ) (cosec θ + cot θ) = 1

⇒ (cosec θ + cot θ) × 1 / 3 = 1

⇒ (cosec θ + cot θ) = 3

**
**

If cosec theta - cot theta = 1/3 then find the value of ( cosec theta + cot theta)

cosec θ - cot θ = 1 / 3 (given)

now, cosec^{2 }θ - cot^{2}θ = 1

⇒ (cosec θ - cot θ) (cosec θ + cot θ) = 1

⇒ (cosec θ + cot θ) × 1 / 3 = 1

⇒ (cosec θ + cot θ) = 3

**
**

What are you looking for?